Dissemination of electronic journals: A content analysis of the library websites of technical university libraries in North India - Vasishta, Seema (Electronic library, 2013)
Analyses the websites of technical university libraries in North India to ascertain whether the libraries are effectively utilising their respective websites to provide trouble-free access to electronic journals available in the library, both those journals subscribed to by the library and via other open source databases relevant to the different courses run by the institution. Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.